Efficacy and safety of tofacitinib modified-release 11 mg once daily plus methotrexate in adult patients with rheumatoid arthritis: 24-week open-label phase results from a phase 3b/4 methotrexate withdrawal non-inferiority study (ORAL Shift). Issue 2 (8th June 2021) - Cohen, Stanley B; Pope, Janet; Haraoui, Boulos; Mysler, Eduardo; Diehl, Annette; Lukic, Tatjana; Liu, Shixue; Stockert, Lori; Germino, Rebecca; Menon, Sujatha; Shi, Harry; Keystone, Edward C
Abstract : Objectives: To report the efficacy, safety and patient-reported outcome measures (PROs) of tofacitinib modified-release 11 mg once daily plus methotrexate in patients with rheumatoid arthritis (RA) from the open-label phase of Oral Rheumatoid Arthritis Trial (ORAL) Shift. Methods: ORAL Shift was a global, 48-week, phase 3b/4 withdrawal study in patients with moderate to severe RA and an inadequate response to methotrexate. Patients received open-label tofacitinib modified-release 11 mg once daily plus methotrexate; those who achieved low disease activity (LDA; Clinical Disease Activity Index (CDAI)≤10) at week 24 were randomised to receive blinded tofacitinib 11 mg once daily plus placebo (ie, blinded methotrexate withdrawal) or continue with blinded tofacitinib 11 mg once daily plus methotrexate for another 24 weeks. Efficacy, PROs and safety from the open-label phase are reported descriptively. Results: Following screening, 694 patients were enrolled and received tofacitinib plus methotrexate in the open-label phase. At week 24, 527 (84.5%) patients achieved CDAI-defined LDA. Improvements from baseline to weeks 12 and 24 were generally observed for all efficacy outcomes (including measures of disease activity, and response, LDA and remission rates) and PROs. Adverse events (AEs), serious AEs and discontinuations due to AEs were reported by 362 (52.2%), 20 (2.9%) and 41 (5.9%) patients, respectively. No deaths were reported. Conclusions: Tofacitinib modified-release 11 mg once daily plus methotrexate conferred improvements in disease activity measures, functional outcomes and PROs, with most (84.5%) patients achieving CDAI-defined LDA after 24 weeks of open-label treatment; the safety profile was generally consistent with the historic safety profile of tofacitinib. Funded by Pfizer Inc; NCT02831855 .